Megaworld Canada - Brauch, Kevin (Stem curriculum resource, 2011)
Discover cutting edge innovations in science and technology from across the Great White North. Step inside the state-of-the-art facilities where Canada's coolest and fastest aerospace and transportation exports are developed, manufactured, and tested. Other possible stories include diamond mining in the Northwest Territories, and the epic ice road that must be built every year to haul the 300,000 tons of fuel, explosives, steel, and concrete needed to operate the mines.